Development of Learning Plan with Midwifery Services Material based on Experiential Learning in ESP - Ardiel, Vonny; Zainil, Yetti; Syarif, Hermawati; Zaim, M. (Proceedings International Conference on Education Innovation and Social Science, 2023)
To create midwifery student professionalism in the topic of learning Midwifery Services, lecturers need a structured learning design. The form of learning in Midwifery services is very suitable using the Experiential learning method. This Experiential learning method has four cycles of phases in shaping the experience of becoming professional in students. The method used in this research is Research and Development. The research subjects were Midwifery students at the Faculty of Health Sciences, Universitas Sumatera Barat. The research object is a Midwifery Service learning topic with learning materials Offering Services, Giving Direction and Persuade. The results obtained are in the form of a Learning Design which contains the learning flow of Midwifery Services in English in the Experiential Learning model. The circular phases are Active Experimentation (Students carry out oral conversation practice based on the theme of conditions experienced every day and Midwifery Services), Concrete Experience (Students are asked to demonstrate the expressions of offering service, giving direction, and persuading in Indonesian Language. The teacher plays video/audio expressions offering service, giving direction, and persuading), Reflective Observation (Learners compare functions, language structures in the utterances heard and compare with English conversation in Midwifery Services), Abstract Conceptualization (Students arrange and make conversations based on the function and structure of linguistic rules using various expressions. Students are given the opportunity to make conversations based on the theme of the conditions experienced in the practice of midwifery services).